2014
DOI: 10.6116/kjh.2014.29.6.165.
|View full text |Cite
|
Sign up to set email alerts
|

Anti-pruritic Effect of Ethanol Extracts from Platycodon grandiflorum and its fermented production in Scratching Behavior Mouse Models

Abstract: Objectives : Platycodon Root is frequently used in traditional medicine to treat inflammatory diseases of the throat. The purpose of this study was to characterize the effect of the EtOH extract of fermented Platycodon grandiflorum on the ameliorative effects on the Antipruritic Effect of atopic dermatitis mouse model induced by compound 48/80 and ovalbumin (OVA)-induced allergic responses in mice. Methods : In the present study, we examined the anti allergic effect of Platycodon grandiflorum (PR) and its ferm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Kim et al (2012) reported that fermented BF by Lactobacillus plantarum (LP), up regulate Th1 cytokines, IL-12, p40 and IFN-γ while the levels of the Th2 cytokines IL-4 and 5 were down-regulated. Ha et al (2014) reported that fermented with Saccharomyces cerevisae decreased the serum levels of Ig E, MDA and reducing Itching reactions in mouse. Oh et al (2010) demonstrate that BF Ext.…”
Section: Post Harvest Processingmentioning
confidence: 98%
“…Kim et al (2012) reported that fermented BF by Lactobacillus plantarum (LP), up regulate Th1 cytokines, IL-12, p40 and IFN-γ while the levels of the Th2 cytokines IL-4 and 5 were down-regulated. Ha et al (2014) reported that fermented with Saccharomyces cerevisae decreased the serum levels of Ig E, MDA and reducing Itching reactions in mouse. Oh et al (2010) demonstrate that BF Ext.…”
Section: Post Harvest Processingmentioning
confidence: 98%